PENGELOLAAN SAMPAH PADA DINAS PASAR KEBERSIHAN DAN TATA KOTA - Irza Setiawan (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2017)
One of problems in Hulu Sungai Utara Regency is garbage. The volume of waste in Amuntai is estimated to reach 100 cubic meters per day, while BPLH only has five trucks and four containers. Each freight carcan only carry as much as six cubic meters. In carrying out the maximum transport of container a day can be done three times to four times. In this research, a qualitative approach is used to solve problemsrelated to Waste Management in Market, Hygiene, and Urban Agency in Waste Management in Upper River North Regency, and the type of research used is descriptive as it is possible in a qualitative approach. Research results include insufficient facilities and infrastructure, lack of human resources, and also lack of community participation in participating in maintaining cleanliness due to lack of socialization. Suggestions given in the form of increasing the budget for the provision of facilities and infrastructure, to provide socialization by using television, radio, and sticker sticking, and held hygiene contest between villages.